1980
DOI: 10.1002/aja.1001580409
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐microscopic cytochemical studies on the secretory process in rat prolactin cells in primary culture

Abstract: Three aspects of the secretory process in male rat prolactin (PRL) cells grown in primary cultures for 7--14 days have been investigated by cytochemical methods. The subcellular localization of prolactin has been studied using preembedding or postembedding immunocytochemical methods after various fixatives. With the postembedding method, PRL is localized essentially in secretory granules. The maximum intensity of staining is obtained with PAF fixative. With the preembedding method, subcellular localization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 22 publications
2
53
0
Order By: Relevance
“…a gift from NIAMDD). As previously reported, these antisera do not cross-react with growth hormone or with any other pituitary hor mone [26]. The specificity of the antisera for hypophysial prolactin was further assessed by immunoblotting for rat anterior pituitary homogenates ( fig.…”
Section: Immunocylochemical Proceduresmentioning
confidence: 69%
“…a gift from NIAMDD). As previously reported, these antisera do not cross-react with growth hormone or with any other pituitary hor mone [26]. The specificity of the antisera for hypophysial prolactin was further assessed by immunoblotting for rat anterior pituitary homogenates ( fig.…”
Section: Immunocylochemical Proceduresmentioning
confidence: 69%
“…With respect to ultrastructural-immunocytochemicai tech nique, the present results can be compared with those from rat pituitary prolactin cells in culture [20], There, also, specificity of immunoreactivity was confirmed with preadsorption controls, and the preembedding method was used successfully. Inter estingly, the intensely stained granules, about 200 nm in diameter, in that study matches quite well with the large immunoreactive granules in neurons, found in the present work.…”
Section: Discussionmentioning
confidence: 96%
“…The acidification of pH may thus be responsible for both the aggregation and the cleavage of SgII in the TGN. Ultrastructural studies have evidenced the aggregation of proteins in specific regions of the more distal part of the TGN in endocrine cells (48), including prolactin cells (49,50). The TGN is a very dynamic structure whose size and shape vary greatly according to the cell type and activity (51,52).…”
Section: Discussionmentioning
confidence: 99%